The complete book of enzyme therapy - Cichoke, Anthony J. (Avery Publishing, 1999)
The Complete Book of Enzyme Therapy gives a clear picture of enzymes -what they are, what they do, and how they can be depleted in the body. It then explains how you can begin an enzyme-rich diet, and when, why, and how enzyme supplements may be taken. Also provided are enzyme treatments for more than 150 conditions.